Nutritional Content Analysis of Tofu Waste in Catfish (Pangasionodon hypophthalmus) Farmer Tangkit Baru Jambi - Bs Monica Arfiana; Sarwo Edy Wibowo; Wulandari Wulandari; Dyah Muji Rahayu; Yatno Yatno (Program Pascasarjana Universitas Sriwijaya, 2022)
One of the factors behind the declining catfish farm in Tangkit Baru, Jambi, is the rising price of commercial feed. A lot of fish farmers stop their cultivation. They make independent feed formulations based on existing sources around them. The lack of knowledge and understanding of feed nutrition causes the feed formulations not necessarily with feed standards (SNI) and feed commercial. Nutritious feed is essential for fish growth. The aim is to compare the nutrition of the tofu waste processed for local fish farmers,